Isolation, Diversity, and Growth-Promoting Activities of Endophytic Bacteria From Tea Cultivars of Zijuan and Yunkang-10 - Yan, Xiaomei; Wang, Zhi; Mei, Yu; Wang, Liqun; Wang, Xu; Xu, Qingshan; Peng, Su; Zhou, Yu; Wei, Chaoling (Frontiers in Microbiology, 2018)
Endophytes are rich in plant tissues and play important roles in plant-microbial interactions and plant-growth regulation. Here, endophytic bacteria from two closely related tea cultivars of Zijuan and Yunkang-10 were isolated, and the diversities were compared. Plant-growth promoting (PGP) activities were determined on the dominant or nitrogen-fixing endophytes from the two cultivars. Endophytic bacteria were isolated by using of different selective media and methods, and the PGP activities were investigated by analytical and molecular technologies. A total of 110 isolates of 18 genera belonging to three phylums (Proteobacteria, Firmicutes and Bacteroidetes) were obtained from Zijuan, while 164 isolates of 22 genera belonging to two phylums (Proteobacteria and Firmicutes) were obtained from Yunkang-10. PGP screening indicated that Herbaspirillum spp., Methylobacterium spp. and Brevundimonas spp. showed different PGP abilities. The PGP ability decreased in order of Herbaspirillum spp., Brevundimonas spp. and Methylobacterium spp., and the majority of Methylobacterium spp. did not showed PGP activity of nitrogen-fixation, P-solubilization, siderophore, indole-3-acetic acid (IAA) production or 1-aminocyclopropane-1-carboxylate (ACC) deaminase. The study of bacterial community and PGP activities confirmed that endophytes in tea plants are constantly changing in different seasons and tea cultivars, and the PGP bacteria in Zijuan are much abundant than those of Yunkang-10.